Influence of calcined clay/limestone, sulfate and clinker proportions on cement performance. (10th August 2020) - Rodriguez, Claudia; Tobon, Jorge I.
Highlights: Calcined clay and limestone promote the hydration of cement at early age. Clinker and CC/L ratio are relevant factors affecting compressive strength. CC/L are confirmed to increase bound water content and AFm phase formation. CC/L influences mechanical strength, bound water content and porosity refinement. Abstract: Clinker (CK), calcined clay to limestone ratio (CC/L), and sulfate content (SO3 ) were studied determining their influence on cement performance. A low-grade kaolinite clay characterized before and after calcination was used. Isothermal calorimetry measurements indicate CK influences mainly energy liberation, while CC/L and SO3 affect kinetics of hydration. Compressive strengths were primarily governed by CK at early age, and its effect is constant throughout hydration; CC/L became relevant as hydration progresses and achieved similar effects as CK beyond 28 d; SO3 (wt%) has marginal contribution only at early age. All cements, including CC/L, obtained higher compressive strengths than their references (CK + quartz mixes). The latter correspond with higher bound water content, carboaluminate hydrates formation, and a finer porous structure estimated by water absorption. Thus, CK and CC/L are most relevant factors in cement performance, and the improvement is proportional to calcined clay content in the mixture.